Population Aging and Economic Growth: Impact and Policy Implications - Jaejoon Lee (Korea Development Institute (KDI), 2019)
- Korea is aging at a faster pace than any other major country, and the negative impact on the economy is expected to be considerable. - In thirty years, the old-age dependency ratio is projected to exceed 70% and GDP growth to mark around the 1% range. This would pose a tremendous threat to sustainability unless the economy makes significant improvements in productivity and the employment structure. - Korea's population aging is proceeding at an unprecedentedly rapid pace while policy responses and institutional reforms fail to keep pace. - Setbacks such as falling labor supply and growth seem to be unredeemable even if Korea's labor force participation rate (by gender and age group) improves to the level of advanced countries. - The labor supply policy to boost the economic participation of the working age population may work as a feasible response to the challenges of population aging to a certain extent. However, it is not enough to make a full recovery given the severe imbalance of Korea's demographic profile. - Policy responses should be focused on reversing the quantitative decline in the labor supply by promoting the participation of the senior labor force while pushing towards the ultimate goal of human capital advancement and higher labor force productivity. - Senior labor force participation can be effective in easing not only the fall in economic growth but also the pressure from the rising dependency ratio. - At the same time, concerted policy efforts should be made in enhancing the general environment including educational and vocational training programs that could upgrade the productivity of the senior population.
Keywords: 330